The Application of Project-Based Learning in Essay Writing within English Essay Writing Course - Ahmad Ryan Tryantama; Miftah Al Farhan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
This study uses semi-structured and observational interviews as data collection methods to examine the impact of PBL on student learning. Findings suggest that implementing PBL in the English Essay Writing Course has a positive effect on student learning. Research shows that switching from traditional teaching methods to PBL can be very effective for courses with important writing topics, such as English essay writing. This study contributes to the understanding of effective teaching methods in English essay writing courses, demonstrating of the step to write an English Essay and the transformative potential of PBL in improving English students' motivation in writing skills. The suggestion is future researchers can do more research on how students explore their writing skills through essay writing at different kinds of essay.